The single farm payment and income risk in Irish farms 2005-2013 - Edward Knapp; Jason Loughrey (Agricultural and Food Economics, 2017)
Agricultural income volatility has become a major hurdle for Irish farmers and policymakers to overcome in their drive to increase investment, production and ultimately income in the sector. This paper studies data from 927 farms in the Teagasc National Farm Survey between 2005 and 2013, the first 9 years of the decoupled subsidy era. The primary income support for European farmers, the single farm payment (SFP), is analysed in the context of its relationship with market income risk, i.e. farm income excluding subsidies. Detrended measures of market income variability are regressed on a large set of control variables. The findings suggest that the amount of SFP received by farmers has a strong and statistically significant relationship with agricultural income volatility.
Keywords: D22; G32; Q12; Q18; 330; Single farm payment; Agricultural policy; Income risk; Risk management; Farm assets